Possible age-related differences in healthcare professionals’ perspectives on younger and older patients’ autonomy and decision-making in the context of sedation in specialised palliative care: exploratory secondary qualitative content and linguistic conversation analysis of interviews with healthcare professionals - Kurkowski, Sandra; Heckel, Maria; Pfaller, Larissa; Peters, Joachim; Jeremias, Bazata; Eva, Schildmann; Ostgathe, Christoph (BMC Palliative Care, 2022)
Background Chronic illnesses and multi-morbidity can threaten competence and independence, particularly in old age. Autonomy becomes increasingly important in the context of sedation, as in this case medication leads to (further) changes of consciousness. The study aimed to identify possible age-related differences in the perspectives of healthcare professionals on patients’ autonomy, in the context of sedation in specialised palliative care. Method Secondary analysis of interviews with healthcare professionals, analysed by qualitative content and linguistic conversation analysis. The interviews analysed span 51 healthcare professionals in specialised palliative care across 17 centres (adult inpatient and specialist palliative home care services) in Germany. Results The study shows that the perspectives of healthcare professionals on patients’ autonomy differs according to the age of the patient in the context of sedation in specialised palliative care. The different perspectives may lead to different ways of treating the patients, for example a greater space of autonomy and decision-making for younger patients. Conclusion In particular, measures that may restrict consciousness (e.g. sedation) and thus influence patients’ ability to fully exercise their autonomy and fully participate in decision-making require special attention by healthcare professionals with respect to possible influences on treatment, such as different perceptions by healthcare professionals based on the patient’s age or age-related stereotype
Keywords: End of life care; Palliative care; Age; Ageing; Autonomy; Qualitative content analysis; Linguistic conversation analysis